Acupuncture for Obstructive Sleep Apnea (OSA) in Adults: A Systematic Review and Meta-Analysis - Wang, Liaoyao (Biomed Res Int, 2020)
OBJECTIVE: Our aim was to assess the efficacy and safety of acupuncture for OSA patients with various severities of the disorder. METHODS: Eight databases including PubMed, Cochrane Library, EMBASE, Web of Science, China National Knowledge Infrastructure (CNKI), Chongqing VIP (CQVIP), Wanfang Data, and Chinese Biomedical Literature Database (CBM) were comprehensively searched till July 2019. Randomized controlled trials (RCTs) testing acupuncture in the treatment of OSA were eligible for inclusion. Studies were selected for inclusion, and data were extracted by two authors independently. The Cochrane Collaboration's Risk of Bias Assessment Tool and RevMan software (version 5.3) were used to evaluate the quality of studies and conduct statistical analysis. RESULTS: Nine RCTs with 584 participants were included. The trials covered acupuncture and electropuncture. Acupuncture caused clinically significant reductions in AHI (MD: -6.18; 95% CI: -9.58 to -2.78; Z = 3.56, P = 0.0004) as well as in ESS (MD: -2.84; 95% CI: -4.80 to -0.16, Z = 2.09, P = 0.04). AHI was reduced more in the subgroup analysis of moderate OSA patients (MD: -9.44; 95% CI: -12.44 to -6.45; Z = 6.18, P < 0.00001) and severe OSA patients (MD: -10.09; 95% CI: -12.47 to -7.71; Z = 8.31, P < 0.00001). ESS was also reduced more in the subgroup analysis of moderate OSA patients (MD: -2.40; 95% CI: -3.63 to -1.17; Z = 3.83, P = 0.0001) and severe OSA patients (MD: -4.64; 95% CI: -5.35 to -3.92; Z = 12.72, P < 0.00001). Besides, acupuncture had a beneficial effect on LSaO(2) (MD: 5.29; 95% CI: 2.61 to 7.97; Z = 3.86, P = 0.0001). The outcome of AHI and LSaO(2) yielded consistent results after sensitivity analysis, but the direction of the outcome of ESS was reversed. And the quality of evidence was mainly low to very low. CONCLUSIONS: Acupuncture therapy is effective for OSA patients in reducing AHI and ESS and in improving the LSaO(2) of various severities, especially in moderate and severe OSA patients. High-quality trials are urgently needed.